2004
DOI: 10.1063/1.1691190
|View full text |Cite
|
Sign up to set email alerts
|

Influence of moisture on device characteristics of polythiophene-based field-effect transistors

Abstract: We investigated a field-effect transistor (FET) based on a poly(3-n-hexylthiophene) (P3HT) to determine the influence of moisture on device characteristics and thus gain a deep understanding of the mechanism underlying the susceptibility to air of the operation of FETs of this kind. The fundamental output characteristics, which include effective field-effect modulation and saturation behavior in the output current, remained almost the same for every current–voltage profile in a vacuum, N2 and O2. By contrast, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
152
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(158 citation statements)
references
References 24 publications
4
152
1
1
Order By: Relevance
“…For these transistors the saturation of the drain current was not observed. This behavior is attributed to the diffusion of H 2 O molecules in the thin film of pentacene which increases the current I off and prevents the saturation of the output characteristics [20]. Moreover, we note that the drain current increases by increasing the gate voltage in all the measurement conditions.…”
Section: Introductionmentioning
confidence: 63%
“…For these transistors the saturation of the drain current was not observed. This behavior is attributed to the diffusion of H 2 O molecules in the thin film of pentacene which increases the current I off and prevents the saturation of the output characteristics [20]. Moreover, we note that the drain current increases by increasing the gate voltage in all the measurement conditions.…”
Section: Introductionmentioning
confidence: 63%
“…In order to further improve organic solar cell performance extracting information about defect states and their role as trapping or recombination centers seems to be crucial. It is well known that P3HT is a conjugated polymer that in exposure to oxygen [3], or moisture [4] results p-doped exhibiting relatively high levels of free carries ( 17 15 10 10  cm -3 ) [5]. Under such conditions, it has been suggested that the P3HT-metal contact forms a Schottky barrier behavior: band bending with a corresponding majority-carrier depletion zone made up at the cathode contact [6,7], due to the presence of acceptor defects (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Before contact is made, there exists an energy offset between the metal and the organic semiconductor work functions, φ c and φ s , respectively, as schematically illustrated in Figure 1B. Donor polymers as poly-(3-hexylthiophene), P3HT can easily undergo oxidation (p-doping) when exposed to the air or moisture, 18,19 producing a change in the hole conductivity. 20 Accordingly, we have proposed very recently that doping of the organic layer produces native mobile charges in the organic blend, which gives rise to the separate equilibration of each contact.…”
mentioning
confidence: 99%